Housing markets & planning policy - Jones, Colin, 1949 January 13-; Watkins, Craig (Chichester, U.K. ; Ames, Iowa : Wiley-Blackwell Pub., 2009)
Housing systems in many countries are now more market-oriented than ever before. This is particularly true of the UK, where there is heightened interest in the ability of the market to deliver new housing, as well as considerable debate among housing academics and policy makers over the extent to which policy instruments can be used to steer market processes. This increased market orientation means a greater understanding of market economics is needed. The challenges of providing affordable housing, while simultaneously addressing the problems of low demand housing in some areas, together with.
Introduction -- The housing problem -- Spatial structure of housing markets -- Understanding housing submarkets -- Dynamics of the housing market -- Planning for the housing market -- Planning policies and the market -- Conclusions and the way forward.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Housing policy -- Great Britain; City planning -- Great Britain; Logement -- Politique gouvernementale -- Grande-Bretagne.; BUSINESS & ECONOMICS -- Real Estate -- General; City planning; Housing policy; Great Britain